«Enfermedad de indio»: sobre el principio patogénico de la alteridad y los modos de transformación en una cosmología amazónica - Barcelos Neto, Aristóteles (2006)
During my field work among the Wauja Indians of the Upper Xingu, I collected several narratives about local people who had suffered animal transformations when they were severely ill. Most of them returned to their human condition after the attention of highly specialized shamans and ritual singers and dancers. This article describes the series of transformations between humans and non-humans in the Wauja cosmology and discusses how the attributes of humanity, animality and monstrosity are distributes and set in relation.